LANSKAP KONTEKS EKSTRALINGUISTIK VIRTUAL DALAM PRAGMATIK SIBER - Kunjana Rahardi (Masyarakat Linguistik Indonesia, 2022)
This study aims to describe the virtual external context landscape in a pragmatic study with a cyber perspective. The research problem of cyber pragmatics is formulated as follows: How is the virtual external context landscape in the perspective of cyber pragmatics? The object of this research is the manifestation of the virtual external context landscape in the perspective of cyber pragmatics. The data of this research are utterances which contain the virtual external context landscape. The data sources of this research are natural texts which contain data about the virtual external context landscape as the source of the substantive data. The source of locational data is natural texts obtained from social media Twitter. The data collection method applied is the see method. The techniques used for listening are recording techniques and note-taking techniques. The last step in data collection is typification so that data types are produced that are ready to be subjected to data analysis methods and techniques. There are two methods applied to analyze the research data, namely the distributional method and the equivalent method. The distributional method is used to reach the linguistic aspects, while the equivalent method is used to reach the external linguistic aspects of this research. The results of this cyber pragmatics research show that the manifestation of the virtual external context landscape is different from the conventional external context landscape. Differences in landscape manifestations can occur in the elements of the context which are the impact of technological developments. In addition, differences in landscape manifestations can also occur in aspects of these context elements as a result of the development of information technology and digital technology as well as internet technology. The landscape aspects of the context elements must be well formulated so that the meaning of speech intentions in the cyber pragmatics perspective can be carried out properly. Inaccuracy in the formulation of the virtual external context landscape will cause the meaning of speech intent to give rise to many misunderstandings. The results of this study are expected to contribute a lot to the development of pragmatics so that pragmatics develops not only systemic pragmatics, general pragmatics, and pragmatics in a culture-specific perspective, but also pragmatics (cyberpragmatics) whose development still needs to be encouraged in Indonesia.